Hygienic assessment of quality and way of life of youth - Kalynychenko, Dmytro (ScienceRise: Medical Science, 2017)
The paper presents the results of the study of life style and quality of female students of higher educational institutions. Aim of research: to estimate life quality indices and their connection with socio-hygienic factors of life activity of girls 17 – 22 years old for substantiating arrangements of the active prophylaxis of health disorders of the female contingent of the early active reproductive age. Materials and methods. 284 female students of higher educational institutions of city Sumy (І group (n= 135)– 17 – 19 years old, ІІ group (n= 149) – 20 – 22 years) took part in the research. Their life quality was estimated using the non-specific questionnaire «SF-36», socio-hygienic factors were studied using the specially elaborated form. Results of research. There were determined quantitative characteristics of the physical (67,03±1,30 points) and psychological (59,69±1,26 points) components of health. Values of physical and psychological components of health of girls 20 – 22 years old are reliably lower comparing with the younger age group (17 – 19 years). Age differences of the parameter “Physical component of health” appear at the expanse of decreasing a mark of the routine role physical functioning and a mark of the general health status of girls 20 – 22 years old comparing with girls of 17 – 19 years. The psychological heath component reliably differed in the chosen age diapasons mainly at the expanse of the role emotional functioning decrease in girls of II group. It was established, that the parameter “General health status” is a system-creating factor of the life quality for the contingent of female students in general by the number of correlations. The role physical functioning, which high mark is connected with the absence of limitations for physical loads, high level of the general health status and emotional condition that helps in everyday activity, is an important factor in the group of girls of 17 – 19 years. Age features of the life quality of female students 20 – 22 years old are in the fact that the social functioning has a reverse correlative connection with the physical functioning, role physical functioning and general health status and prove the fact of the priority of the high level of the motivation, volitional effort, purposefulness for providing the high level of the social functioning. Conclusions. The life quality of female students depends on a series of socio-hygienic factors, such as: education of the mother, physical activity level, smoking, alcohol intake, pathologies of the respiratory system, digestion, nervous and reproductive systems. Quantitative characteristics of the dependence of the life quality on the complex of factors allow to substantiate arrangements of the prophylaxis of health disorders of the female contingent of the early reproductive age scientifically